Portraits of place: images of Southern Africa in landscape painting. - Lammas, Rebecca Caroline (My University, 1993)
Place is an elusive but vibrant geographical entity. It comprises the human facet of the environment that is textured by subjective impulses and collective ideologies. The meaning of places is symbolically expressed in art: geographical myths are generated, perpetuated and anticipated in literary and visual creative images. In South Africa, the opportunities for using art to understand place have rarely been explored. Local geographers are more comfortable in the sterile landscapes born of theoretical and quantitative analysis than with their emotional and imaginative reconstitution as art. Yet, an abundance of indigenous qualitative material awaits sensitive investigation. Tracing the fingerprints of social and personal imagery in landscape painting illuminates the sense of place in southern Africa. The local environment has been interpreted variously through the lenses of colonialism, nationalism and a contemporary resistance movement as a foreign, alien, silent and violent landscape. Articulating the myths in visual terms, .painters offer the geographer a bridge into southern Africa as it is confronted by the people who live here. Art is a celebration of the human environment; landscape paintings are portraits of place
Keywords: Landscape painting -- South Africa.; South Africa -- Description and travel.